2013
DOI: 10.1177/0001699313479954
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing female labour market reserves

Abstract: With an ageing population and a persistent booming economy, Norway is already facing an unmet demand for labour. Considering the country's high female part-time work rate, more full-time work among women constitutes a potential labour reserve. This article investigates factors that encourage transitions into full-time work and discourage transitions out of fulltime work based on panel data from the period 2003-2009. Shifts between working-time status are linked to human capital, occupational characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Apart from current or completed family care demands, other factors may influence women’s labor supply, such as child-rearing activities, the household’s socioeconomic situation, or partner’s characteristics. Previous studies have shown that homemaking women with school-aged children are more likely to enter part-time or full-time employment than those with preschool children (Drobnič, 2000; Drobnič, Blossfeld, & Rohwer, 1999), whereas the transition from part-time to full-time work is not dependent on the age of children, indicating that part-time work is a rather robust work–family reconciliation strategy (Kitterød, Rønsen, & Seierstad, 2013; O’Reilly & Bothfeld, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from current or completed family care demands, other factors may influence women’s labor supply, such as child-rearing activities, the household’s socioeconomic situation, or partner’s characteristics. Previous studies have shown that homemaking women with school-aged children are more likely to enter part-time or full-time employment than those with preschool children (Drobnič, 2000; Drobnič, Blossfeld, & Rohwer, 1999), whereas the transition from part-time to full-time work is not dependent on the age of children, indicating that part-time work is a rather robust work–family reconciliation strategy (Kitterød, Rønsen, & Seierstad, 2013; O’Reilly & Bothfeld, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Within the group of homemaking or part-time working women, inequalities will emerge from differences in educational investments and labor market experience prior to interrupting employment or reducing working hours. Higher education and previous labor market experience may increase women’s chances to find employment and put them in a better bargaining position to obtain a full-time job (Drobnič et al, 1999; Gash, 2008; Kitterød et al, 2013; O’Reilly & Bothfeld, 2002). In addition to human capital resources, a stronger career orientation can lead to higher propensity for employment and longer working hours (Gangl & Ziefle, 2015; Stam, Verbakel, & de Graaf, 2014; Vlasblom & Schippers, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…First, working in occupations with strong norms for part-time employment and fewer full-time job opportunities might restrict the transition to full-time work. For example, Kitterød et al (2013) found that transitions from part-time employment to full-time employment are less likely in occupations in the health and service sector. Similarly, in many jobs in the hospitality industry, comparably high shares of all jobs are atypical and allow for fewer opportunities for career advancement (Ilsøe et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Next, there is a substantive gender gap in part-time working, also in Finland (Eurostat, 2021), and therefore our controls include gender. Having a partner, especially one with a high income, may also impose more childrearing responsibility on women, affecting their full-time employment probability, as well as the future employment trajectory (Kitterød et al, 2013). Moreover, being or becoming a mother, and a young age are associated with more vulnerable labor market positions (Kuitto et al, 2019).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation